Answer:
2
b
+
9
m
+
6
x
+
10
Step-by-step explanation:
2
b
+
4
+
6
x
+
6
+9
m
2
b
+
6
x
+
10
+
9m
2
b
+
6
x
+
9
m
+
10
= 2
b
+
9
m
+
6
x
+
10
Answer:
No solution
Step-by-step explanation:
6X - 3Y = -9--------------(1)
- 2 X +Y= 5---------------(2)
from equation two,
Y = 5+2X------------------(3)
substitute equation (3) into equation (1)
6X-3(5+2X)= -9
opening bracket
6X-15-6X= -9
6X- 6X = -9+15
0 = 6
<h2>therefore the answer is no solution</h2>
Answer:
x = -2, y=1
Step-by-step explanation:
x-7y=-9---------------------equation 1
-x+8y=10-------------------equation 2
From equation 1, make x the subject of formula
x=7y-9----------------------equation 3
substituting x=7y-9 in equation 2,
-(7y-9)+8y=10
Expanding bracket
-7y+9+8y=10
Collecting like terms
8y-7y=10-9
y=1
substituting y=1 in 3
x=7(1)-9
x=7-9
x=-2
Answer:
it is so hard men and there is no solution maybe you can search on siri